Превентивні заходи реагування поліції на правопорушення: досвід Грузії - Чумак, В. В.; Chumak, V. V.; ORCID: http://orcid.org/0000-0002-6171-2250 (Вісник Запорізького національного університету. Юридичні науки. - 2015. - № 2 (1). - с. 95-101., 2015)
Досліджено превентивні заходи реагування поліції на правопорушення в Грузії, звернено особливу увагу на порядок проведення цих заходів, на права поліцейського та особи, щодо якої проводиться профілактична робота. З огляду на зарубіжний досвід розроблено шляхи вдосконалення чинного законодавства України у сфері попередження та протидії злочинним правопорушенням.

Indicated that crime prevention - the main direction of the state and society in the fight against this phenomenon and “force” component of executive power of any state is the police that is designed to perform law enforcement functions. Emphasized that the police Georgia is an independent state institution, which has a characteristic structure and management system and uses its methods. Determined that the police are taking steps to respond to offenses under the current legislation of Georgia in the areas of administrative law, criminal law and other regulations. Investigated the preventive measures of police response to crime in Georgia, paid special attention to the order of these activities, the police and the rights of a person whom carried preventive work and taking into account international experience. Ways of improving the current legislation of Ukraine on the prevention and combating of criminal offenses, including:  to develop what measures should apply law enforcement to deal with different kinds of offenses;  outline the procedure for prevention;  to determine the scope of persons to be involved in the implementation of preventive measures and to articulate the rights and responsibilities of all members of the event;  to provide law enforcement officials with necessary technical equipment. A special role in enhancing the effectiveness of preventive measures plays use of science. The most promising is the use of laser and other optical techniques to monitor traffic, detect and prevent crime, use of video and photography, the use of special tools for surface examination of a person, vehicle, etc., the use of electronic monitoring is an effective preventive measure recidivism;  take into account individual and age characteristics of a person against whom preventive measures are used, special attention should be paid to minors.

Исследованы превентивные меры реагирования полиции на правонарушения в Грузии, обращено особое внимание на порядок проведения этих мероприятий, на права полицейского и лица, в отношении которого проводится профилактическая работа. Учитывая зарубежный опыт, разработаны пути совершенствования действующего законодательства Украины в сфере предупреждения и противодействия преступным правонарушениям.
Чумак, В. В. Превентивні заходи реагування поліції на правопорушення: досвід Грузії / В. В. Чумак // Вісник Запорізького національного університету. Юридичні науки. - 2015. - № 2 (1). - с. 95-101.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; Грузия; Грузія; превентивні заходи; превентивные меры; поліція; полиция; preventive measures; police; Georgia